If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(h + -3) = 15 Reorder the terms: 5(-3 + h) = 15 (-3 * 5 + h * 5) = 15 (-15 + 5h) = 15 Solving -15 + 5h = 15 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 5h = 15 + 15 Combine like terms: -15 + 15 = 0 0 + 5h = 15 + 15 5h = 15 + 15 Combine like terms: 15 + 15 = 30 5h = 30 Divide each side by '5'. h = 6 Simplifying h = 6
| 2x+7x=18x | | 360/n=90 | | 9X(X+1)=O | | 2x^2+37x=35 | | 2x-(3x+6)=4x-46 | | 10^3•10^-5•10^10/10^6 | | 2y-5x=-9 | | 6x-1=2x+16 | | 3(78-20)=n | | 3807=47(p+20) | | 5n-2=n+2 | | 350=14(3x+7) | | 5/8a=25 | | 12j+15=-20+5j | | 80=8(2x-4) | | C=3.14(46) | | Log2/y | | 5(x+14)=140 | | 4x^3-8x^2-6x+4=0 | | C=3.14(19) | | 36345.8=8.6(36504.9n) | | 160=20(2x-10) | | 8x+-3.8=-8x+-7 | | F(500)=1.5x+300 | | 5x+5=2X+4 | | 160=24(2x-5) | | (3x^2-14x-5)/(x-5) | | C=2(3.14)(21) | | 1440=36(3x+10) | | 10x+6=166 | | F(200)=1.5x+300 | | C=3.14(26) |